Filling analysis of artificial lateral canals after main canal obturation through three different endodontic sealers - Tiago André Fontoura de Melo; Denise Pereira Nunes; Fernanda de Carvalho Modaffar Al-Alam; Alexandre Azevedo Salles; Renata Grazziotin Soares1 (Revista Sul-Brasileira de Odontologia, 2015)
This study aimed to evaluate, in vitro, the filling ability of lateral canals after main canal obturation through three different endodontic sealers. Material and methods: Thirty single-rooted pre-molars were used and, six lateral canals were constructed on proximal surfaces and arranged in pairs at 3, 5 and 7 mm from the apex. After chemo-mechanical preparation, with size #40 memory instrument, the teeth were randomly assigned to three experimental groups, according to the root canal sealer applied: Endofill® (group A), Sealer 26® (group B) and MTA Fillapex® (group C). In all groups, we used active lateral condensation technique with gutta-percha associated with sealer. After obturation, the teeth were radiographed at buccolingual direction and the images were digitized. The analysis of endodontic sealer plug near the lateral canals was performed by calculating the area through Image Tool® software. Results and Conclusion: The data were subjected to parametric (Anova), and nonparametric (Kruskal-Wallis) tests, with significance level of 5%. There was no difference among the tested sealers for filling the lateral canals. Concerning to the positions of lateral canals, no differences were also found among sealer types, except at 7 mm from the apex, where MTA Fillapex® showed a significantly greater filling than Sealer 26®.